2014
DOI: 10.1016/j.cattod.2013.11.056
|View full text |Cite
|
Sign up to set email alerts
|

Alumina-grafted SBA-15 as a high performance support for Pd-catalysed cinnamyl alcohol selective oxidation

Abstract: eprints@whiterose.ac.uk https://eprints.whiterose.ac.uk/ Reuse Unless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or other rights-holder may allow further reproduction and re-use of this version -refer to the White Rose Research Onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 58 publications
7
43
0
Order By: Relevance
“…Parlett et al observed productivity of 56 mmol.g -1 .h -1 with PdO-meso alumina and 42.5 mmol.g -1 .h -1 with Pd-gamma alumina catalysts [2]. The values reported in blue solvents were slightly higher but comparable with the results obtained in this study.…”
Section: Catalytic Acitivity Of Zn-mn Oxide and Zn-mn Oxide/fmwcntssupporting
confidence: 89%
See 1 more Smart Citation
“…Parlett et al observed productivity of 56 mmol.g -1 .h -1 with PdO-meso alumina and 42.5 mmol.g -1 .h -1 with Pd-gamma alumina catalysts [2]. The values reported in blue solvents were slightly higher but comparable with the results obtained in this study.…”
Section: Catalytic Acitivity Of Zn-mn Oxide and Zn-mn Oxide/fmwcntssupporting
confidence: 89%
“…The aldehydes have been usually synthesized with a stoichiometric amount of oxidizing agents such as dichromate, hypochlorite, permanganates, and others [1][2][3]. These oxidant were harmful and environmental malignant, expensive, and yield a large amount of byproducts [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The expected hexagonally close-packed channels of the SBA-15 mesopore network were observed in all cases, with surface areas and mesopore diameters decreasing with successive TiO 2 grafting cycle (Figure 2 and Figure S1), reflecting pore narrowing and partial blockage of micropores in the silica framework [31]. Uniform mesopores of 6.3 nm diameter were in accordance with previous reports [29].…”
Section: Resultssupporting
confidence: 89%
“…20 The results indicated that these samples retained a highly ordered structure of SBA- 15 23 whereas the Si 2p XPS spectra also exhibited two BEs, 103.4 and 102.3 eV, assigned to Si−O−Si and Al−O−Si, respectively (Figure 1). 23 The same results also were observed in the XPS spectra of Al 2 O 3 @SBA-15 (not data shown). In addition, FTIR spectra also show that the surface Si−OH groups of SBA-15 at 966 cm −1 disappeared with the loading of aluminum oxide (SI Figure S5).…”
Section: ■ Results and Discussionmentioning
confidence: 98%